1994
DOI: 10.1073/pnas.91.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana contains two differentially expressed 3-hydroxy-3-methylglutaryl-CoA reductase genes, which encode microsomal forms of the enzyme.

Abstract: The enzyme 3-hydroxy-3-methylglutarylCoA reductase (HMGR; EC 1.1.1.34) catalyzes the first ratelimiting step in plant isoprenoid biosynthesis. Arabidopsis thaliana contains two genes, HMGI and HMG2, that encode HMGR. We have doned these two genes and analyzed their structure and expression. HMGI and HMG2 consist of four exons and three small introns that interrupt the coding sequence at equivalent positions. The two genes share sequence similarity in the coding regions but not in the 5'-or 3'-flanking regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 42 publications
(42 reference statements)
13
157
0
1
Order By: Relevance
“…Aside from suberin, phellem imperviousness has been attributed to the associated waxes, which in cork consist mainly of isoprenoids such as triterpenes and sterols (Castola et al 2005). This is in agreement with the cork oak upregulation of the gene coding for 3-hydroxy-3-methylglutaryl coenzyme A reductases (HMGR1), which catalyses the first rate-limiting step in the isoprenoid biosynthesis (Enjuto et al 1994) and with the upregulation of several genes related to wax biosynthesis (Table S6A), hence suggesting a higher accumulation of these compounds in the outer bark of cork oak.…”
Section: Discussionmentioning
confidence: 55%
“…Aside from suberin, phellem imperviousness has been attributed to the associated waxes, which in cork consist mainly of isoprenoids such as triterpenes and sterols (Castola et al 2005). This is in agreement with the cork oak upregulation of the gene coding for 3-hydroxy-3-methylglutaryl coenzyme A reductases (HMGR1), which catalyses the first rate-limiting step in the isoprenoid biosynthesis (Enjuto et al 1994) and with the upregulation of several genes related to wax biosynthesis (Table S6A), hence suggesting a higher accumulation of these compounds in the outer bark of cork oak.…”
Section: Discussionmentioning
confidence: 55%
“…HMGR from many plant species has been characterized, and its activity has been shown to be regulated by different physiological and environmental stimuli, such as phytohormones, light, wounding, pathogen attack, feedback mechanisms, and endogenous protein factors (for reviews, see Bach et al, 1991aBach et al, , 1991bStermer et al, 1994). Although the intracellular site(s) of mevalonate synthesis has been a matter of controversy for many years (Gray, 1987), recent data support the hypothesis that, in higher plants, the formation of mevalonate occurs solely in the cytosol (Enjuto et al, 1994).…”
Section: Introductionmentioning
confidence: 75%
“…Arabidopsis (Caelles et al, 1989;Enjuto et al, 1994), three genes have been reported in Hevea brasiliensis (Chye et al, 1992), and four genes are present in tomato . Larger HMGR gene families have been reported in wheat (Aoyagi et al, 1993), pea (Monfar et al, 1990 and A. Boronat, unpublished results), and potato (Stermer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the prophase, 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR) catalyzes mevalonate synthesis from HMG-CoA, which is considered the most important committed step of the MVA pathway (Choi et al, 1992). Subsequently, in the metaphase, farnesyl diphosphate synthase (FPPS), a representative and crucial enzyme, condenses IPP and DMAPP to form the key direct precursor, Farnesyl diphosphate (FPP) (Enjuto et al, 1994). After a branchpoint intermediate for various terpenoids based on FPP, Squalene Synthase (SQS) drives the synthesis of triterpenoids, sterols and cholesterols.…”
Section: Fig 1 Triterpenoid Biosynthetic Pathway In Ganoderma Cellsmentioning
confidence: 99%